Pengembangan Media Pembelajaran Matematika - Silva Andini Ayu Aprilla (JoEMS (Journal of Education and Management Studies), 2019)
This research aims to determine the feasibility of learning media based on multimedia on trigonometry material using Adobe Flash CS 3 Professional application. This research uses with a ADDIE model. Data analysis was done by using quantitive descriptive data analysis. The result of data analysis of validation expert assessment of materials (Lecturer in Mathematics Education Mather Fitri Umardliyah, M.Pd.) there are 4,25 to the category of very valid, validation expert of assessment of materials (Teacher of mathematic Mr. Sumarno, S.Pd.) contained 4,0 with a valid category. While there are 4,3 with media (Lecturer of Technology of Information Mrs. Siti Sufaidah, S.Kom., M.Si.) expert with a very valid category. Meanwhile, the result of students responses contained 84% in very good category. This result indicate that learning media based on multimedia on trigonometry material using Adobe Flash CS 3 Professional application feasible and gets a positive responses from students it means students are enthusiastic in using learning media and learning media based on multimedia on trigonometry material using Adobe Flash CS 3 Professional application can helps the students in receiving the learning materials.